2020
DOI: 10.1093/mnras/staa194
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray emissivity of low-density stellar populations

Abstract: The dynamical production of low-mass X-ray binaries and brighter cataclysmic variables (CVs) in dense globular clusters is well-established. We investigate how the X-ray emissivity of fainter X-ray binaries (principally CVs and coronally active binaries) varies between different environments. We compile calculations (largely from the literature) of the X-ray emissivity of old stellar populations, including open and globular clusters and several galaxies. We investigate three literature claims of unusual X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 222 publications
1
21
0
Order By: Relevance
“…In this way, Cheng et al (2018a [104]) have shown that dynamical interactions are less dominant than previously believed, and that the primordial formation channel has a substantial contribution. That result was also supported more recently by Heinke et al (2020 [94]), though these authors also discuss some caveats in the work by Cheng et al (2018a [104]) which could have influenced their conclusions. Another interesting and striking result by Cheng et al (2018a [104]) is that, unlike what has been previously thought, the faint X-ray populations are under-abundant in GCs with respect to the Solar neighbourhood and Local Group dwarf elliptical galaxies.…”
Section: Pos(golden2019)013supporting
confidence: 72%
See 3 more Smart Citations
“…In this way, Cheng et al (2018a [104]) have shown that dynamical interactions are less dominant than previously believed, and that the primordial formation channel has a substantial contribution. That result was also supported more recently by Heinke et al (2020 [94]), though these authors also discuss some caveats in the work by Cheng et al (2018a [104]) which could have influenced their conclusions. Another interesting and striking result by Cheng et al (2018a [104]) is that, unlike what has been previously thought, the faint X-ray populations are under-abundant in GCs with respect to the Solar neighbourhood and Local Group dwarf elliptical galaxies.…”
Section: Pos(golden2019)013supporting
confidence: 72%
“…A large fraction of 'exotic' sources in GCs are X-ray emitters (see Heinke et al 2020 [94] PoS(GOLDEN2019)013…”
Section: Correlation Between the Number Of Cataclysmic Variables And mentioning
confidence: 99%
See 2 more Smart Citations
“…However, lower-density clusters are theoretically expected to have more primordially-formed CVs than dynamically formed CVs (Davies 1997;Belloni et al 2019), and indeed there is strong observational support for this (Kong et al 2006;Haggard et al 2009;Cheng et al 2018;Belloni et al 2019). The strength of the correlation between stellar encounter rate and X-ray sources (which varies depending on the sample) has been recently discussed by Cheng et al (2018) and Heinke et al (2020).…”
Section: Introductionmentioning
confidence: 93%